Comparative field study to evaluate the performance of three different traps for collecting sand flies in northeastern Italy. Issue 2 (December 2013) - Signorini, M.; Drigo, M.; Marcer, F.; di Regalbono, A. Frangipane; Gasparini, G.; Montarsi, F.; Pietrobelli, M.; Cassini, R.
ABSTRACT Three standard methods for collecting sand flies (sticky trap, CDC light trap, and CO2 trap) were compared in a field study conducted from June to October, 2012, at a site located in the center of a newly established autochthonous focus of canine leishmaniasis in northeastern Italy. Six traps (two sticky traps, two CDC light traps, and two CO2 traps) were activated at the same time for a single night every two weeks during the season of sand fly activity. A total of 5, 667 sand flies were collected and 2, 213 identified, of which 82.1% were Phlebotomus perniciosus, 17.4% P. neglectus, 0.3% Sergentomya minuta, and 0.2% P. mascitti. The performances of all traps were influenced by their position inside the site, increasing with proximity to the animal shelters. CO2 traps were more attractive for females of P. perniciosus and P. neglectus. CDC light traps showed an intermediate efficiency and were more attractive for P. neglectus, compared to other two traps. Results suggest that in northern Italy the CO2 trap is a suitable sampling method for sand fly monitoring programs that include transmitted pathogen surveillance.